Safety and efficacy of intrathecal ziconotide in the management of severe chronic pain - Howard S Smith; Timothy R Deer (Dove Medical Press, 2009)
Howard S Smith,1 Timothy R Deer21Albany Medical College, Department of Anesthesiology, Albany, New York, USA; 2The Center for Pain Relief, Clinical Professor, West Virginia, University, Charleston, West Virginia, USAAbstract: Ziconotide is a conopeptide intrathecal (IT) analgesic which is approved by the US Food and Drug Administration (FDA) for the management of severe chronic pain. It is a synthetic equivalent of a naturally occurring conopeptide found in the venom of the fish-eating marine cone snail and provides analgesia via binding to N-type voltage-sensitive calcium channels in the spinal cord. As ziconotide is a peptide, it is expected to be completely degraded by endopeptidases and exopeptidases (Phase I hydrolytic enzymes) widely located throughout the body, and not by other Phase I biotransformation processes (including the cytochrome P450 system) or by Phase II conjugation reactions. Thus, IT administration, low plasma ziconotide concentrations, and metabolism by ubiquitous peptidases make metabolic interactions of other drugs with ziconotide unlikely. Side effects of ziconotide which tend to occur more commonly at higher doses may include: nausea, vomiting, confusion, postural hypotension, abnormal gait, urinary retention, nystagmus/amblyopia, drowsiness/somnolence (reduced level of consciousness), dizziness or lightheadedness, weakness, visual problems (eg, double vision), elevation of serum creatine kinase, or vestibular side effects. Initially, when ziconotide was first administered to human subjects, titration schedules were overly aggressive and led to an abundance of adverse effects. Subsequently, clinicians have gained appreciation for ziconotide’s relatively narrow therapeutic window. With appropriate usage multiple studies have shown ziconotide to be a safe and effective intrathecal analgesic alone or in combination with other intrathecal analgesics.Keywords: pain, ziconotide, intrathecal analgesics, safety, patient acceptability